Hubungan tingkat pendidikan ibu dan pengetahuan ibu tentang 1000 HPK dengan kejadian stunting pada balita 0-59 bulan - Nurlaili Nurlaili; Alkhair Alkhair; Hairunnisah Hairunnisah; Nur Husnul Khatimah (Holistik Jurnal Kesehatan, 2026)
Background: Stunting is a major public health issue, with prevalence rates remaining above the WHO critical threshold. At the family level, a mother's formal education and accurate understanding of the first 1000 days of life period are key pillars determining a child's nutritional status and growth. Purpose: To analyze the relationship between maternal education levels and knowledge regarding the first 1000 days of life period and the incidence of stunting in children aged 0-59 months. Method: This observational analytic study, utilizing a case-control design, was conducted in the working area of ​​the Rasanae Timur Community Health Center, Bima City, between February and March 2026. The study sample consisted of 89 mothers with children aged 0–59 months. Primary data were collected using a structured questionnaire regarding education and knowledge concerning the "First 1,000 Days of Life" period, while stunting status was determined through direct anthropometric measurements analyzed using WHO Anthro software. Data were statistically analyzed using the Chi-Square (χ²) test with a significance level of p < 0.05. Results: Bivariate analysis showed a highly significant relationship between maternal education levels and stunting incidence (p< 0.001); 40.6% of mothers with low education levels had stunted children, compared to 7.0% of mothers with high education levels. Additionally, a significant relationship was found between maternal knowledge regarding the first 1000 days of life period and stunting (p < 0.001), with the highest incidence of stunting observed in the group of mothers with poor knowledge (66.7%), compared to those with adequate (7.1%) or good (14.3%) knowledge. Conclusion: Maternal education levels and knowledge regarding the first 1000 days of life period are significantly associated with the incidence of stunting in children. Strengthening cognitive literacy focused on specific phases within the first 1000 days of life cycle is crucial for inclusion in behavior change intervention programs aimed at preventing stunting.   Keywords: 1000 First Days of Life; Maternal Education; Maternal Knowledge; Stunting.